208 Prognostic significance of the central tumor size (CTS) in stages IIB and IIIB bulky cervical cancer (CC): proposing a new FIGO staging system. (18th September 2019) - Soderini, A; Aragona, A; Moschen, H; Mendez, M; Quintaie, A; Bonavia, E; Rosa, G; Rodriguez, Y; Cuneo, N
Abstract : Objectives: The aims of the present study were: 1) to define the prognostic significance of the CTS in stages IIB and IIIB cervical cancer and its impact on disease-free survival (DFS) and overall survival (OS) rates; 2) to propose a new FIGO Staging System for CC based on this evidence. Methods: R etrospective study including 450 pts. between 1/2007 to 9/2011 FIGO stages IIB (229 pts.) and IIIB (221 pts.) cervical cancer (cc) . MRI was added to mesure the CTS. It was stratified in ≤ -3.99 cm, 4–5.99 cm, 6–7.99 cm & >8 cm. The disease-free survival (DFS) and overall survival (OS) related to tumor size.were analyzed . Results: The median age were 45 & 49 years old for stages IIB & IIIB groups. Median Follow up: 45 months. The DFS & OS rates were: stage IIb, 58.5% & 64%; and 40% and 43% for the IIIb, respectively The DSF and OS rates were 65, 1% and 71, 5% in CTS between 4- 5.99cm, vs 27, 7% and 36.6% for CTS >6 cm (p<0, 001) in stages IIb. In the stage IIIB ones, DSF and OS rates were 58, 3 & 57% in CTS between 4–5.99 cm Vs 25% & 28.5%, , with CTS >6 cm (p<0.001). These results were independent of histological type and treatment received. Conclusions: Patients with CTS >6 cm ihad a worse prognosis. These FIGO Stages could be modified into IIb1 & IIb2; and IIIb1 & IIIb2, with a 6m cut off. It is needed a personalized treatment strategy for those cases.